2002
DOI: 10.1159/000066796
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mycophenolate Mofetil on Kallikrein Expression in the Kidney of 5/6 Nephrectomized Rats

Abstract: It has recently been proposed that tubulointerstitial damage plays a key role in the pathogenesis of sodium-dependent hypertension. Since components, enzymes and substrates, of the kallikrein-kinin system (KKS) are synthesized by connecting and collecting tubules, respectively, it is expected that damage of any origin, involving the tubulointerstitial compartment, may affect the functionality of these nephron segments and impair blood pressure control. Therefore, we analyzed renal kallikrein expression in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…It has been reported that male rats with 5/6 Nx have a significant reduction in urinary kallikrein activity and in renal kallikrein expression, 13 which is compatible with the renal structural abnormalities and the severe reduction in functional renal mass described in this model. The possible role of reduced kallikrein in some of these alterations is under discussion.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It has been reported that male rats with 5/6 Nx have a significant reduction in urinary kallikrein activity and in renal kallikrein expression, 13 which is compatible with the renal structural abnormalities and the severe reduction in functional renal mass described in this model. The possible role of reduced kallikrein in some of these alterations is under discussion.…”
Section: Discussionsupporting
confidence: 76%
“…In addition to the abnormalities characteristic of chronic renal failure, such as decreased GFR, moderate hypertension, and glomerular disease, 10 5/6 Nx is associated with alterations in the renin-angiotensin-aldosterone and kallikrein-kinin systems. [11][12][13] …”
mentioning
confidence: 99%
“…The staining score was expressed as density per millimeters squared. This method of quantification has been validated in previous publications (4,5).…”
Section: Image Analysis Of Immunohistochemistry and In Situ Hybridizamentioning
confidence: 85%
“…Previous experiments have also indicated that adenovirus mediated HK gene delivery significantly attenuated gentamycin-induced nephrotoxicity and enhanced renal function [13]. The renal protective effects of the KKS have been demonstrated in several hypertensive rat models with progressive renal injury [10,[14][15][16][17]. Together, these findings suggest that a repressed renal KKS may play an important role in the pathogenesis of chronic renal failure and that delivery of the HK gene may represent a novel approach to treat chronic renal failure.…”
Section: Introductionmentioning
confidence: 88%
“…Dahl-salt sensitive rats, which have salt-induced hypertension, exhibit a dysfunctional kallikrein-kinin system (KKS) and are more susceptible to kidney injury than spontaneously hypertensive rats which have similar blood pressure [9]. Decreased kallikrein expression in the kidney of 5/6 nephrectomized rats was recently reported [10]. Dr. Yu and colleagues demonstrated that polymorphisms in the human tissue kallikrein gene promoter are etiologic effectors of hypertension and hypertension-associated end-stage renal failure [11].…”
Section: Introductionmentioning
confidence: 99%